BOARD GAME SEBAGAI MEDIA PENGENALAN RAGAM SAYURAN UNGUPADA ANAK USIA 6-12 TAHUN DI KOTA PALEMBANG - Nando Ramadhon; Mukhsin Patriansah; Yosef Yulius (VisArt: Jurnal Seni Rupa dan Design, 2023)
Abstract: Vegetables are leaves (like mustard), plants (bean sprouts), pods or seeds (capri, chickpeas) etc. that can be cooked (KBBI, 2012). The main study of this research focuses on identification, analysis and design on board game prototype works and other supporting media. This design uses design thinking planning methods including premedia, main media and follow up media. Data was collected through, observations, questionnaires, interviews, literature and websites. The data is then identified, classified, selected, then analyzed using the method (5W+1H),and interpreted according to the text and context. The design of the board game Social Campaign as a medium for introducing various vegetables to children aged 6-12 years is used as a visual communication medium which is in this design discussion. This design aims to introduce purple vegetables and the benefits of purple vegetables to the target audience, namely children aged 6-12 years. In this design, the media produced are board game s, posters, t-shirts, books, pens, pouches, tumblers, bags, and hats.